Assay of Progressive Antithrombin in Plasma - Abildgaard, U; Gravem, K; Godal, H. C (Thrombosis and Haemostasis, 1970)
A simple two-stage assay of progressive antithrombin activity in plasma is described. After heat defibrination, plasma is diluted VlO in buffer (pH 8.0) and incubated with thrombin for 3 min at 37° C. After incubation, residual thrombin activity is determined with standard substrate (antithrombin clotting time). By substituting buffer for diluted plasma, the buffer clotting time is determined. The antithrombin activity may be calculated from these two clotting times or read from a standard curve. It is expressed in per cent of pooled normal plasma. The range in 36 normal plasmas was 74-116%, the S. D. 11%, and the S. E. M. 5.7%. The combination of simplicity and accuracy makes the present method compare favourably with earlier methods.